A Critical Analysis in McDonald’s X BTS “THE BTS MEAL” Advertisements: A Multimodal Perspective - Ernanda, Enggar (Language Horizon: Journal of Language Studies, 2023)
This qualitative study aims to investigate the visual and linguistic elements and their interplay given in food advertisements. Five selected advertisements related to McDonald’s X BTS “THE BTS MEAL” were collected online and analysed by using theory from Cheong (2004) on Generic Structure Potential and Visual Grammar theory proposed by Kress and Van Leeuwen (2006). From the research results obtained, Lead, Display, and Emblem are the visual elements existed in the advertisements, along with the Primary Announcement, Secondary Announcement, Enhancer, and Tag for linguistic elements. The interplays found in the study are representations, engagements, and processes. A representation is presented of how BTS is a model, and colour is one of the visual elements that play important part in meaning-making. In engagement, it is shown how the advertisers attract the attention of potential buyers by using modality, gaze, and the social distance. Placement of the BTS members in the same central part as the advertised products thereby provides an equal value of products and models in the same form. The interplay between those elements are evidenced of how all aspects contribute to leaving a greater impression towards the intended audience of the BTS Meal products.